The Legal Dimension of 3D Printing: Analyzing Secondary Liability in Additive Layer Manufacturing - Reddy, Preeta (Science and Technology Law Review, 2014)
Additive manufacturing, commonly known as 3D printing, allows for the construction of highly-customizable, detailed, three-dimensional objects using a different mechanism than traditional manufacturing. This technology has already yielded innovative developments in medicine, fashion, art, manufacturing, and several other fields. However, 3D printing is not without controversy. As 3D printers and compatible designs become more publicly accessible, users can engage in illegal activity such as copyright, trademark, patent infringement, or printing of contraband and otherwise-regulated materials such as drugs or weapons. This Note addresses these legal issues in the context of analogous technologies, focusing especially on copyright issues. The Note then advocates for direct regulation of 3D printing.